2004
DOI: 10.1002/bjs.4596
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative mortality following oesophagectomy and problems in reporting its rate

Abstract: Operative mortality rates following oesophagectomy have continued to fall. However, the true rate is almost certainly higher than that reported here, for a variety of reasons. The 1-year survival of patients was only reported in about a quarter of the papers. It may be a more meaningful figure than postoperative mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
162
3
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(184 citation statements)
references
References 11 publications
16
162
3
3
Order By: Relevance
“…22,23 It is now argued that 1-year survival rates following surgical resection give a better indication of the true mortality outcomes in oesophageal cancer. 24 The 1-year survival rates give some guidance about the degree of patient selection and whether or not the operation was really worthwhile. Our results compare favourably with the 1-year survival rates of approximately 61% from a number of Western series unadjusted for staging from the 1990s.…”
Section: Table 2 Waiting Times To First Treatment January 2000 To Maymentioning
confidence: 99%
“…22,23 It is now argued that 1-year survival rates following surgical resection give a better indication of the true mortality outcomes in oesophageal cancer. 24 The 1-year survival rates give some guidance about the degree of patient selection and whether or not the operation was really worthwhile. Our results compare favourably with the 1-year survival rates of approximately 61% from a number of Western series unadjusted for staging from the 1990s.…”
Section: Table 2 Waiting Times To First Treatment January 2000 To Maymentioning
confidence: 99%
“…However, despite improvements in perioperative care, the operations are not without risk. Reviews of international studies concluded that postoperative death rates following oesophageal cancer operations were 8.9% in western countries (Jamieson et al, 2004), and that 30-day death rates following gastrectomy for cancer were 7.6% (Grossmann et al, 2002). Prognostic factors for postoperative hospital death after upper gastrointestinal tract (GI) cancer operations have been studied using multivariable logistic regression models comprising patient-related and hospital-related variables.…”
mentioning
confidence: 99%
“…A review of esophagectomy outcomes for the 1990's showed a 8.8% in hospital mortality rate for this decade [26], although lower mortality (<5.0%) was observed in high volume centres [27]. More recent reports from the 2000's describe mortality rates of 3-5%, again with lower mortality rates consistently reported from high volume centres [28].…”
Section: Discussionmentioning
confidence: 99%